Primary Cell Wall Modifying Proteins Regulate Wall Mechanics to Steer Plant Morphogenesis - Qiu, Dengying; Xu, Shouling; Wang, Yi; Zhou, Ming; Hong, Lilan (Frontiers in Plant Science, 2021)
Plant morphogenesis involves multiple biochemical and physical processes inside the cell wall. With the continuous progress in biomechanics field, extensive studies have elucidated that mechanical forces may be the most direct physical signals that control the morphology of cells and organs. The extensibility of the cell wall is the main restrictive parameter of cell expansion. The control of cell wall mechanical properties largely determines plant cell morphogenesis. Here, we summarize how cell wall modifying proteins modulate the mechanical properties of cell walls and consequently influence plant morphogenesis.